(untitled) (Huellas, 2022)
The process of energy transition is reflected in the transformation of landscapes. The progressive incorporation of increasingly modern energy technologies opens debates in European countries around their landscape integration and the social perception. In Argentina, the energy landscapes do not attest so far relevance as a subject of analysis in the academic field. Faced with the lack of antecedents, this exploratory paper seeks to take the landscape as a category of geographical analysis on the past and present use of wind energy. Its objective is to study the patrimonial valorization and the socio-environmental challenges, resulting from the transformation of the landscapes, by the materialization of the energy transition. To this end, it opts for a qualitative methodology and different space-time scales of analysis. The work reconstructs the heritage legacy of the wind from old low-power facilities for milling, water pumping and electricity production that are revalued by society. It also makes a preliminary analysis of the emerging wind landscapes after the start-up of large wind farms in certain regions of the country. The new landscapes created by the installation of wind turbines produce very diverse reactions in communities, ranging from acceptance to social rejection, including neutrality or indifference.